Effect of freeze storage on hemicellulose degradation and enzymatic hydrolysis by dilute-acid pretreatment of Mongolian oak. (1st February 2016) - Jeong, Han-Seob; Jang, Soo-Kyeong; Kim, Ho-Yong; Yeo, Hwanmyeong; Choi, Joon Weon; Choi, In-Gyu
Abstract: The objective of this research was to investigate the effect of freeze storage on the efficiency of hemicellulose degradation and enzymatic hydrolysis by dilute-acid pretreatment of Mongolian oak. The freeze storage of Mongolian oak was conducted depending on several factors (freezing time, solid to freezing solution ratio, and freezing solution type) before dilute-acid pretreatment process of constant condition. The results showed that the major contents of reducing sugars and their degradation products in the liquid hydrolysates were slightly increased until a freezing time of 120 min. The xylose content was the highest (18.22 g/100 g initial input) at a specific solid to freezing solution ratio of 5:3 (w/v), while the sugar degradation product contents were not remarkably increased at these points. Based on these conditions, when distilled water was used as the freezing solution, glucose yield was maximized (36.20% of initial input (conversion rate of 87.92%)) after enzymatic hydrolysis to a greater degree than control.